Effect of Physiotherapy Combined with MOTOmed Viva2 on Motor Function of Children with Cerebral Palsy - Chuntao ZHANG; Zhenhuan LIU; Malan ZHANG (康复学报)
Objective:To observe the effect of physiotherapy combined with MOTOmed viva2 on motor function of children with cerebral palsy (CP).Methods:Forty CPchildren were randomly assigned to MOTOmed group (n=20) and conventional therapygroup (n=20). The MOTOmed group received MOTOmed viva2 and conventional therapy, and the conventional therapy group received conventional therapy only. Two groups received therapy for twenty minutes each time, five times per week, twenty times for one small course, twenty days rest after each small course, and three small courses for a big course. Before and after one course of treatment, the Modified Ashworth Scale (MAS), D and E dimensions of gross motor function measure (GMFM-88) and gait parameter of two groups were evaluated.Results:After one course of treatment, each index in the two groups had significant improved compared with that before treatment (P<0.05), and the degree of improvement in MOTOmed group was higher than that of conventional therapy group (P<0.05).Conclusion:MOTOmed viva2 has good effects on motor function of CP children, and the effect is better than that of conventional physiotherapy therapy.